(untitled) - Irokawa, Daikichi (New York, 1995)
An insider's account of the development of a modern superpower offers a reassessment of Emperor Hirohito's incredible sixty-year reign, spanning the Depression, World War II, Hiroshima and Nagasaki, and the explosive recovery and growth of postwar Japan.
Keywords: Japan; History; Shōwa period, 1926-1989.